Determination of effectiveness of combined mastitis vaccines prepared for dairy cows in mice - H. Hüseyin Hadimli; Zafer Sayın; Kürşat Kav; Osman Erganiş; Hülya Türütoğlu; Dursun Ali Dinç (Eurasian Journal of Veterinary Sciences)
Aim: In this study, the development of combined mastitis vaccines for different bacterial mastitis agents (Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus agalactiae, Corynebacterium bovis and Trueperella (Arcanobacterium) pyogenes), the determination of effectiveness of vaccination on humoral immunity and the ratio of morbidity and mortality against challenge trials in mice was aimed. Materials and Method: Two combined mastitis vaccines (with ginseng extract, aluminium hidroxide or mineral oil adjuvants) were prepared strains of S. aureus, S. epidermidis, Str. agalactiae, C. bovis and T. pyogenes isolated from clinical and subclinical mastitis cases in dairy cows. Mice were vaccinated twice at interval 5 days before parturition by combined mastitis vaccine with aluminum hydroxide or mineral oil. Blood samples were taken at 10th days after second vaccination. ELISA kits for each mastitis agents were prepared and the antibodies titers were measured by ELISA in samples. Results: The levels of antibodies for each agents in sera of all vaccinated mice were significantly higher than that of controls. S. aureus, S. epidermidis, Str. agalactiae, C. bovis and T. pyogenes were administered to mice for challenge trials at 10th days after second vaccination. Mice were observed for 20 days for determination of occurrence of morbidity and mortality. No mortality and morbidity were occurred in all vaccinated mice. Conclusion: Combined mastitis vaccines prepared by different bacterial agents causing mastitis were found to be effective in mice.